2017
DOI: 10.1177/1536012117724558
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Myocardial Fatty Acid and Glucose Metabolism in Fasted and Nonfasted Spontaneously Hypertensive Rats Using MicroPET/CT

Abstract: Using longitudinal micro positron emission tomography (microPET)/computed tomography (CT) studies, we quantified changes in myocardial metabolism and perfusion in spontaneously hypertensive rats (SHRs), a model of left ventricular hypertrophy (LVH). Fatty acid and glucose metabolism were quantified in the hearts of SHRs and Wistar-Kyoto (WKY) normotensive rats using long-chain fatty acid analog 18F-fluoro-6-thia heptadecanoic acid (18F-FTHA) and glucose analog 18F-fluorodeoxyglucose (18F-FDG) under normal or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
1
Order By: Relevance
“…These animals were obtained from an unrelated longitudinal study of perfusion, and fatty acid and glucose metabolism dysfunction using PET/CT. 16 The hearts of all SHRs exhibited LVH, confirmed by in vivo myocardial positron emission tomography studies. 16 In a second 2-year study from 2011 to 2012, it was again confirmed that the SHR model exhibits abnormal perfusion and metabolism.…”
Section: Imaging Protocolmentioning
confidence: 65%
See 1 more Smart Citation
“…These animals were obtained from an unrelated longitudinal study of perfusion, and fatty acid and glucose metabolism dysfunction using PET/CT. 16 The hearts of all SHRs exhibited LVH, confirmed by in vivo myocardial positron emission tomography studies. 16 In a second 2-year study from 2011 to 2012, it was again confirmed that the SHR model exhibits abnormal perfusion and metabolism.…”
Section: Imaging Protocolmentioning
confidence: 65%
“…16 The hearts of all SHRs exhibited LVH, confirmed by in vivo myocardial positron emission tomography studies. 16 In a second 2-year study from 2011 to 2012, it was again confirmed that the SHR model exhibits abnormal perfusion and metabolism. 17 Anesthetic overdose of isoflurane was used after which the heart was removed and the chambers flushed with saline solution delivered through the arterial valves.…”
Section: Imaging Protocolmentioning
confidence: 65%
“…32 The discrepancy among these investigations may be attributable to the severity of HF, where in the early stages there is a normal (or slightly elevated) rate of fatty acid oxidation, with a downregulation in advanced stage of HF. 10 In all of our imaging studies 33,34 glucose metabolism was consistently elevated in the hypertensive SHRs compared to the normotensive WKY controls. When fed, the fatty acid metabolism in the SHRs was less than with the WKY controls.…”
mentioning
confidence: 75%
“…33 Whereas with fasting, there was an observed increase (though not significant) in fatty acid metabolism in the SHR model compared with WKY controls. 34 Metabolic changes appear to precede mechanical changes of LVH progression in the SHR model.…”
mentioning
confidence: 98%
“… 14 Another group observed in older SHR (8–22 months of age), by longitudinal imaging with small animal positron emission tomography (PET)/computed tomography, increased glucose and fatty acid utilization at 8 months of age that was sustained up to 20 months. 15 , 16 Decreased systolic function and increased cardiac volume occurred only at 20 months.…”
mentioning
confidence: 99%